(untitled) (Namibia Educational Reform Forum Journal, 2019)
The purpose of this study was to compare the Grade 12 learners’ performance in Direct Algebraic equations and Word Problem equations. Data were collected from school X in Oshana region. The study sought answers to the following two questions: “How does the performance of learners in Word Problem Equations (WPE) compare with Direct Algebraic Equations (DAE)?” and “What is the correlation between the performance of learners in WPE and DAE?”. The mixed method was used to collect the data from the sample from 19 learners who were randomly selected to take part in this study. The study employed written tests as instruments for data collection in this study. It was found that both qualitative and quantitative data indicated a lower performance in WPE as compared to DEA. On the relationship between the performance of learners in DAE and WPE the study found a weak positive correlation (r=0.446). The study also found t that the weaker comprehension of WPE was fueled by learners’ limited fluency in translating the wordy mathematical problems into direct equations that they could then manipulate algebraically.